Problems in Interpretation - Biscaye, Elizabeth (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractThe Government of the Northwest Territories currently provides interpreting and translating services in French, English and seven northern aboriginal languages. Simultaneous interpreting was, until recently, only delivered in Inuktitut. With increasing demand, and improvements to training programs, it is now provided in the Dene languages as well. Relay interpreting, a unique feature to the NWT interpreting services, plays an important role due to the multiple languages dealt with on a regular basis. This paper will discuss the importance of, and problems encountered with, simultaneous interpreting in the NWT.